Peoples of the Middle East and North Africa...40 Years On - Bowen, Jon; Johnson, Hillary; Jenson, Lindsay (My University, 2012)
In 1972, National Geographic Magazine published ?Peoples of the Middle East,? an insert map that it distributed to all subscribers. As in all regions of our dynamic world, much has changed. The purpose of this study was to create a revised map to capture some of this change as part of an effort to bring our image of the Middle East and North Africa into the 21st century.
Color poster with text, images, and maps.
Keywords: Middle East--Civilization--History--20th century; Middle East--Civilization--History--21st century; Africa, North--Civilization--History--20th century; Africa, North--Civilization--History--21st century; Middle East--Maps; Africa, North--Maps; Posters